Remastering Ubuntu Menjadi Perangkat Lunak Pendukung Laboratorium Teknik Iinformatika STMIK Sinar Nusantara Surakarta - Ristya Andinim, Bebas Widada, Sri Tomo (Jurnal Ilmiah SINUS, 2014)
The purpose of this study to support the lecture with an alternative legal software, free lectures and support activities on campus, especially in the Laboratory of Information Engineering STMIK Sinar Nusantara. The analysis shows that the Sinar Nusantara STMIK Surakarta not fully utilize the software that supports open source and not many human resources that meet the IT business based in STMIK Sinar Nusantara opensource. In business it is intended for the implementation of cost savings this kind of technology, using open source software (Linux). To that end, the author makes a software supporting opensource based Laboratory Informatics legal and ready to use. Data collection methods include field studies and literature. This study uses a survey as a method of questionnaires distributed to respondents as a way to gather information about their experience in using open source software based. And for planning the use of software that runs on Linux, giving any alternative open source software that can be used and function is similar to the official software that is being used today. Author gives equal weight to 4 variables (free, userfriendly, stable and feature completeness) to conduct elections open source software that will be used.Keyword : STMIK Sinar Nusantara, software, open source, Linux